Development and validation of a cost-effective DIY simulation model for McDonald cerclage training - Buechel, Johanna; Kalisz, Adam; Herbert, Saskia Laureen; Scherer-Quenzer, Anne; Blau-Schneider, Bettina; Starrach, Teresa; Kraft, Katrina; Wöckel, Achim; Pecks, Ulrich; Kiesel, Matthias (Archives of Gynecology and Obstetrics, 2024)
Purpose: The prevention of preterm birth is a challenging task for obstetricians. Cervical cerclage, used as both a primary and secondary prevention method for spontaneous preterm birth, is a crucial surgical intervention. It is essential that obstetricians can learn this procedure in a simulated environment before performing the stitches on high-risk patients. This study aimed to develop a simulator based on 3D printing and evaluate its validity for clinical training. Methods: The objectives of this study were (1) to design and construct a cost-effective simulator for McDonald cerclage with two different cervix models—a closed cervix and a cervix with bulging membranes—using common material from a DIY store and 3D printing technology and (2) to validate its effectiveness through feedback from learners and experts in cervical cerclage. The self-made simulator was evaluated by obstetricians using a questionnaire with Likert scale. Results: Obstetricians and gynecologists assessed the simulator and found it useful for learning and practicing cervical cerclage. The simulator was deemed valuable for skill training. Conclusion: Cervical cerclage is a complex procedure that should be mastered through simulation rather than initial practice on real patients. Our simulator is a cost-effective model suitable for various clinical settings. It has been validated by obstetricians for both preventive and therapeutic cerclage, demonstrating its efficacy for training in cerclage techniques. Future research should focus on less skilled obstetricians and gynecologists and investigate how repeated use of the simulator can enhance their performance in cerclage stitching.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Cervical stitch; High-risk pregnancy; Preterm birth; Skills training; Surgical training